A PCR-Based Assay Targeting the Major Capsid Protein Gene of a Dinorna-Like ssRNA Virus That Infects Coral Photosymbionts - Montalvo-Proaño, Jose; Buerger, Patrick; Weynberg, Karen D.; van Oppen, Madeleine J. H. (Frontiers in Microbiology, 2017)
The coral-Symbiodinium association is a critical component of coral reefs as it is the main primary producer and builds the reef’s 3-dimensional structure. A breakdown of this endosymbiosis causes a loss of the dinoflagellate photosymbiont, Symbiodinium, and/or its photosynthetic pigments from the coral tissues (i.e., coral bleaching), and can lead to coral mortality. Coral bleaching has mostly been attributed to environmental stressors, and in some cases to bacterial infection. Viral lysis of Symbiodinium has been proposed as another possible cause of some instances of coral bleaching, but this hypothesis has not yet been experimentally confirmed. In this study, we used coral virome data to develop a novel PCR-based assay for examining the presence and diversity of a single-stranded RNA (ssRNA) virus by targeting its major capsid protein (MCP) gene. Illumina sequence analysis of amplicons obtained with novel primers showed 99.8% of the reads had the closest taxonomic affinity with the MCP gene of the virus, Heterocapsa circularisquama RNA virus (HcRNAV) known to infect dinoflagellates, indicating that dinorna-like viruses are commonly associated with corals on the Great Barrier Reef. A phylogenetic analysis of MCP gene sequences revealed strong coral species specificity of viral operational taxon units (OTUs). This assay allows a relatively easy and rapid evaluation of the presence and diversity of this particular viral group and will assist in enhancing our understanding of the role of viral lysis in coral bleaching.